How does a team's virtuality impact knowledge transfer effectiveness among its members?: A multi-mediator-moderator model. Issue 6 (26th April 2021) - Chen, Xiaogang; Carpenter, Darrell; Su, Libo
ABSTRACT: A thorough understanding of how organisational teams behave effectively in the ever increasingly virtual setting has become integral to team success. One such vital team behaviour is the transfer of knowledge among team members (i.e. knowledge transfer). Two divergent views of team virtuality and its impact on knowledge transfer effectiveness have been presented in the literature. Our approach to addressing this research gap is to identify the mediating pathway between virtuality and knowledge transfer effectiveness and identify the contingent conditions of the mediating pathway. We test our research model through a quasi-experimental study. The results establish a sequential link among virtuality, the transactive memory system, open communication climate, and knowledge transfer effectiveness in a team context. Further, the results show that the timing of virtuality has intricate influences on the overall nature (i.e. being positive or negative) of virtuality's impact on knowledge transfer effectiveness.